2021
DOI: 10.24875/ric.20000064
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' Attitudes, Knowledge, and Perceived Barriers toward Fertility Preservation in Young Breast Cancer Patients in a Developing Country

Abstract: ‡ Villarreal-Garza and Martinez-Cannon are both to be considered first authors as they contributed equally to this manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Studies show that reproductive education plays a positive role in improving disease-related knowledge and relieving reproductive concerns [29] . Doctors with a stronger sense of responsibility are more willing to communicate with patients and provide effective consultation [30] .…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that reproductive education plays a positive role in improving disease-related knowledge and relieving reproductive concerns [29] . Doctors with a stronger sense of responsibility are more willing to communicate with patients and provide effective consultation [30] .…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, 24% of physicians wrongly considered pregnancy and 20% GnRHa use during chemotherapy to be detrimental to the prognosis of BC. 41 Such misconceptions and neglect towards interventions aimed at fertility preservation are not restricted to the Latin American region; a report from East Asia also describes a reduced uptake on fertility preservation strategies due to lack of discussions and referrals to fertility specialists. 42 …”
Section: Fertility Counseling and Preservationmentioning
confidence: 99%
“…In fact, high cost is regarded as one of the most significant barriers for fertility preservation. 41 , 43 , 44 Without insurance coverage, access to fertility preservation strategies is only through out-of-pocket spending, and for a large proportion of BC patients in LMICs, these treatments are unaffordable. 39 , 45 This was illustrated in the previously mentioned 2017 Mexican survey, as only 3% of the surveyed patients considered themselves able to afford extra expenses beyond oncologic treatment.…”
Section: Fertility Counseling and Preservationmentioning
confidence: 99%
“…An extensive systematic review showed that6 66%–100% of patients with cancer expressed a need for fertility information, particularly among young, childless patients with reproductive plans. However, due to a lack of fertility knowledge,7 8 low awareness of fertility preservation,9 a severe shortage of fertility-related information support services10 and a vast selection of fertility preservation therapies,11 it appears to be more challenging for young female patients with cancerto make fertility preservation decisions consistent with their preferences and values in the short period between diagnosis and treatment initiation. The 2018 American Society of Clinical Oncology clinical practice guidelines recommend12 that healthcare professionals should discuss the feasibility of preserving fertility with female patients with cancer who wish to preserve their fertility as early as possible prior to treatment in order to provide patients with more options.…”
Section: Introductionmentioning
confidence: 99%